Pengaruh Penambahan Pasir Terhadap Tingkat Kepadatan dan Daya Dukung Tanah Lempung Lunak - Prasenda, Christian; Setyanto, Setyanto; Iswan, Iswan (Universitas Lampung, 2015)
The problem of strength and resilience of soil is one of things that really need to considered in theplanning and construction work of a civilian building . This is because the land in question servesas a medium that holds the load or the action of a construction that is built on it . Stabilizationusing sand material is one way to meet the needs of the required strength . Changes in weatherand temperature in the field are factors that makes the ground unstable .The type of soil is soft clay stabilized from the Rawa Sragi village, Jabung District, East LampungDistrict. This research was conducted by using a mixture of sand with variations mixture of 5%,10% and 15%. After the CBR testing, Density, Atterberg Limits and Specific Gravity for eachsample.The more variations of a mixture of sand were added resulting in declining water levels that wouldmake the value of the soil carrying capacity increases, the value of density and plastic limitincreased, while the value of the liquid limit and plasticity index decrease.Keywords: sand, soft clay, bearing